Evaluation of an interphalangeal-joint prosthetic hand in trans-radial prosthesis users - Sutthison N. (2023)
Background: A body-powered functional and cosmetically appeasing hand with moving interphalangeal joints (IPJ-Hand) was created. Function and satisfaction with the IPJ-Hand, conventional hand (CH) and functional hook (FH) in trans-radial prosthesis users were evaluated. Methods: Eight participants with trans-radial amputations were provided with three prosthetic hands and performed the Nine Hole Peg Test (NHPT), Brief Activity Measure of Upper Limb Amputees (BAM-ULA) and Quebec User Evaluation of Satisfaction with Assistive Technology QUEST). Results: The data are shown as the median and interquartile range (IQR) due to skewed data distribution. Differences across hands were seen in NHPT with CH 57 (13.3), FH 49.5 (26.5), IPJ-H and 49 (14.8) seconds respectively. BAM-ULA, 10 (1.5), FH 10 (0.7), and IPJ-Hand 10 (1.7). QUEST scores, FH 28.5 (7.2) with the highest score, IPJ-Hand 26 (6.8), and lastly CH 25.5 (9.2). Conclusion: Individual participant results varied, with some participants performing better on the NHPT when using the IPJ-Hand when compared to the CH and FH. No differences between hands on the BAM-ULA were seen, and although no large differences in QUEST were observed, users performed best using IPJ-Hand.Key messages An interphalangeal joint prosthetic hand (IPJ-Hand) offers the similar function of a prosthetic hook, and the appearance of a conventional hand, but with improved dexterity. Minimal resources are needed to create the IPJ-Hand for prosthesis wearers.